La estética del secreto en una novela de espionaje : La deuxième mort de Ramón Mercader de Jorge Semprún - Kroll, Simon (Acta Hispanica, 2015)
This paper examines a specificcharacteristic of spy novels, the aesthetics ofsecrecy, on the example of Jorge Semprún's Ladeuxième mort de Ramón Mercader. An importantaspect in the creation of an aesthetic of secrecyin the novel in question is the variation of thefamous figure of the double. Ramón Mercader,the protagonist of the novel presents aninteresting case of this, which will be analysedin the first part of this paper. The second partof the article points out the overrulingorganisation principle of the novel: the secret.The complex narratological and temporalstructure of the novel obeys to the secret,which makes it the major formal principle ofthis text. The story does not only narrate secretsbut the secret as a formal principle creates atext with plenty of voices and a complextemporal structure, contributing to the creationof an aesthetic of secrecy.